REJUVENATING THE PLACEMAKING POTENTIAL OF BLUE-GREEN INFRASTRUCTURE: LOHIA CANAL GREATER NOIDA - Singh, Kamini; Kumar, Bipasha; Verma , Kanika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The blue-green network plays a vital role in conserving the urban ecosystem by acting as a sponge and absorbing climate extremes. In cities 70% of the precipitation is lost due to inefficient drainage systems. The network of urban water bodies plays a crucial role to retain this water, encourage groundwater recharge and to prevent flooding. However, the urban design and planning processes often neglect the diverse potential of the blue-green infrastructure and the adjoining buffer spaces along the drains, canals, and rivers.The research identifies the Lohia canal in Greater Noida as a potential pedestrian and cycle network, a social space, and an eco-sensitive zone for conservation of existing biodiversity and develops an applied research framework. The research methods are primary field studies, interviews, mapping, and photography along the 8 kms stretch of canal to identify issues associated with the negligence of the canal in urban settings. This study is utilized to develop an integrated vision for revitalization of three layers of canal that are – 1. the climatic resilience, 2. the urban ecology and 3. the social spaces. The scheme thus proposes intervention at the seven locations for placemaking and ecological restoration through a series of connected and integrated design interventions.